Duopolistic competition on a plane - Davit Maskharashvili (Charles University in Prague, Institute of Economic Studies (IES), 2019)
The paper models duopolistic competition in so called monotowns: towns with one big factory where most of the citizens are employed. Workers after job go to one of the competitor shops, buy the product and bring it home. Nash equilibrium is found for linear and two-dimensional cases. The principle of maximum differentiation is refuted.
Keywords: C72; D43; L13; R32; 330; spatial competition; two-dimensional city